The Effect of Green Accounting, Green Intellectual Capital & Corporate Social Responsibility on Financial Performance: Empirical Study of Energy Sector Companies Listed on the Indonesian Stock Exchange for the 2021-2023 Period - Riski, Muhammad; Husnatarina, Fitria; Umbing , Golda Belladonna; Christmas, Andreas Fajar; Nasir, Darmae; Yeremi, Ryant Nicolas Hasiholan; Ludang, Ribka Febiola Agus (Manunggal Halim Jaya, 2025)
This research examines the impact of green accounting, intellectual capital, and corporate social responsibility on Indonesia's energy companies' financial performance. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. The independent variables used in this study are green accounting, green intellectual capital, and corporate social responsibility, while the dependent variable is financial performance. This research employs multiple regression analysis with observations from 2021 to 2023. The data used in this study were obtained from financial statements and sustainability reports. This research found that green accounting, intellectual capital, and corporate social responsibility do not significantly impact financial performance. This suggests that energy sector companies have not fully prioritized environmental sustainability and social responsibility in managing their operations.